Comparison of body size, relative growth and size at onset sexual maturity of Uca uruguayensis (Crustacea: Decapoda: Ocypodidae) from different latitudes in the south-western Atlantic - Hirose, Gustavo Luis; Fransozo, Vivian; Tropea, Carolina; López-Greco, Laura S.; Negreiros-Fransozo, Maria Lucia [UNESP] (Cambridge University Press (CUP), 2013)
Some crustaceans show variations of their reproductive biology within their geographical distribution, and knowledge about such variations is important for the comprehension of their reproductive adaptations. This study compared two populations of the fiddler crab Uca uruguayensis from two locations on the south-western Atlantic coast: Ubatuba Bay, São Paulo, Brazil and Samborombón Bay, Buenos Aires, Argentina. The population features analysed were the body size variation (carapace width = CW) and the size at the onset of sexual maturity (SOM) in order to test the hypothesis that the size at SOM, should be the same in relative terms (RSOM), independently of the latitudinal position. In the Brazilian population the CW ranged from 4.18 to 11.60 mm for males and 3.90 to 9.80 mm for females, and in the Argentinean population from 3.60 to 14.10 mm for males and 2.85 to 12.00 mm for females. In the Brazilian population the SOM was 7.1 (RSOM = 0.58) and 5.9 mm CW (RSOM = 0.57) for males and females, respectively, and in the Argentinean population it was 7.0 (RSOM = 0.42) and 6.75 mm CW (RSOM = 0.53) for males and females, respectively. This fact is probably related to a great plasticity in the life history features of Uca uruguayensis under different environmental conditions. © 2012 Marine Biological Association of the United Kingdom.
Keywords: allometry; Argentina; Brazil; crab size; fiddler crab; latitudinal; variation; body size; crab; environmental conditions; geographical distribution; growth rate; latitude; latitudinal gradient; reproductive biology; sexual maturity; Atlantic Ocean; Atlantic Ocean (Southwest); Buenos Aires [Argentina]; Samborombon Bay; Sao Paulo [Brazil]; Ubatuba Bay